SISTEM INFORMASI MANAJEMEN PENYEWAAN LAPANGAN FUTSAL DI KOTA MATARAM MENGGUNAKAN METODE PROTOTYPING - Putra, Nathanael Lucky Hadi; Rosika, Herliana; Akhyar, Halil (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2025)
The inefficiency in the futsal field rental process in Mataram City, which still relies on manual methods such as booking by telephone or booking directly, results in delays in confirmation and potential recording errors. This research aims to develop a web-based Futsal Field Rental Management Information System to streamline the booking and payment process. The proposed system allows tenants to make reservations and payments online while assisting field owners in managing rental data and creating financial reports automatically, thereby increasing efficiency and accuracy. The system was developed using the prototyping method, which allows the creation and refinement of the system in stages through early versions (prototypes) that are evaluated by users, so that feedback can be integrated directly in each development cycle. System testing conducted using the Blackbox method shows that the developed system can function properly, simplify the ordering process, reduce recording errors, and improve business operational efficiency. In addition, testing was also carried out using the Mean Opinion Score (MOS) method to evaluate user satisfaction from a subjective perspective, providing insight into the perceived usability and acceptance level of the system. In conclusion, the implementation of this system effectively answers the challenges in futsal field rental by providing a faster, transparent, and efficient solution for both tenants and managers.